The Effect of Website Quality, Information Quality, Buyer Trust on Purchase Decisions at Online Shop (Shopee) in DKI Jakarta - Theodorus Gavrilla Banusetyo; Resti Hardini; Kumba Digdowiseiso (Jurnal Syntax Admiration, 2023)
This study aims to determine Website Quality, Information Quality and Buyer Trust in Purchase Decisions at Shopee's online shop in DKI Jakarta. The data analysis technique is multiple linear regression and uses the SPSS program. The results of this study indicate that there is an influence between Website Quality on Purchase Decisions seen from the tcount value of 2,214 and significant. For Purchase Decisions, it can be seen from the tcount that is equal to 3.131 and is significant. For Buyer Trust on Purchase Decisions, which can be seen from the tcount value, which is 3,490 and significant. Partially or stimulus has a strong influence among the three variables, the most significant is the Buyer Trust variable (X3). The results of this study expect Trust to increase Buyer Trust (X3) which can support Purchase Decisions.